The fauna of Tell Nebi Mend (Syria) in the Bronze and Iron Age—a diachronic overview. Part 2: hunting, fowling and fishing. (July 2015) - Grigson, Caroline; Edwards, Yvonne; Cerón-Carrasco, Ruby
<x content-type="archive" xml:space="preserve">Abstract</x> The diversity of wild mammals and birds remains excavated from Tell Nebi Mend indicates the presence of wetlands in the vicinity of the Tell, as well as access to woodland, steppe and desert. The Late Bronze Age assemblages revealed differences in hunting and fowling strategies employed by the people using the east and west sides of the Tell, those on the east having a marked preference for large, perhaps prestigious, mammals, aurochsen, wild boar and bears; those on the west, for gazelles, small game and birds. Fish were also available locally. The presence of certain geese, ibis and Nile perch may imply contact with Egypt. The pattern of change among the mammalian remains suggests gradually increasing aridity from the Middle Bronze Age onwards, buffered by the propinquity of the rivers Orontes and Mukadiyah.